?COMPARATIVE SALT TOLERANCE STUDIES ON DIFFERENT PLANT SPECIES (SESBANIA AEGYPTICA, SESBANIA ACULEATA, ELUSINE CORACANA, SORGHUM BICOLOR ANDSORGHUM SODANESE) (Biological Sciences - PJSIR, 1994)
Comparative salt tolerance and cell sap composition for Na, K, Ca and Cl of 4 plant species Sesbania aegyptica, S. aculeata, Elusine coracana, Sorghum bieolor and S. sodanese was studied using different salinity levels of control, EC 5,10,15 and 20 dS m. Results indicate that fresh and dry weights of shoots decreased with increasing salinity. A 50% reduction in the whole plant biomass was observed in dhancha at a much higher salinity level as compared to other plant species. Sodium and chloride concentrations in leaf sap of four plant species increased with increase in salinity while K and Ca decreased significantly.